2023
DOI: 10.2217/nnm-2022-0233
|View full text |Cite
|
Sign up to set email alerts
|

Nanotherapeutic Potential of Antibacterial Folic Acid-Functionalized Nanoceria for Wound-Healing Applications

Abstract: Aim: The functionalization and characterization of antibacterial nanoceria with folic acid (FA) and elucidation of their in vivo wound healing application. Materials & methods: Functionalization of nanoceria were done with FA using a chemical method and their antibacterial activity, cellular biocompatibility and in vivo wound healing application were evaluated. Results: The functionalization of nanoceria with FA was done with 10 to 20 nm size and -20.1 mV zeta potential. The nanoformulation showed a bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Intracellular ROS generation was measured by DCFDA staining according to [ 44 ]. Cells were divided into five groups and treated according to the doses as previously mentioned in Sect.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular ROS generation was measured by DCFDA staining according to [ 44 ]. Cells were divided into five groups and treated according to the doses as previously mentioned in Sect.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the bactericidal and biofilm inhibition effects of the folate-decorated liposomes incorporating vancomycin was higher compared to direct vancomycin application, suggesting superior MRSA targeting and delivery of the drug [90]. The targeting potential of folate functionalization was also confirmed by the superior targeting and antibacterial enhancement of the efficacy of folate-functionalized cerium NPs [91]. This has been widely exploited in PDT studies.…”
Section: Antibacterial Photodynamic Therapy Folate Targetingmentioning
confidence: 97%
“…ZnO NPs were seen to reduce the expression of IL-1β, IL-6, and TNF-α in a dose-dependent manner in RAW 264.7 cells. ROS causes inflammation by initiating lipid peroxidation in the phospholipid membrane [169,170]. Controlling ROS formation, therefore, helps ZnO NP anti-inflammatory activity ZnO NPs reduce the expression of pro-inflammatory genes and proteins, allowing for the treatment of inflammatory illnesses.…”
Section: Doxorubicin Hepg2 Cellsmentioning
confidence: 99%